Integrating Indigenous Knowledge Systems in Entrepreneurship: A Case of Horticulture Farmers in Mutoko District of Zimbabwe - Shingirai S. Mugambiwa (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
Entrepreneurship plays a significant role in eradicating poverty and providing sustainable livelihoods for communities. Governments, non-governmental organizations, and community development agencies are on the trail to consider rural entrepreneurship as an economic empowerment strategy in the developing world. Given the shortcomings of the Western entrepreneurship skills widely employed in many communities, this study assesses the role and significance of an approach that is place-based and rooted in local cultures that are associated with long-settled communities with strong ties to their natural environments. Nevertheless, a plethora of entrepreneurial strategies employed is foreign to local communities, which makes it difficult to produce the anticipated outcome vis-à-vis sustainable development. The study employs a qualitative method and an exploratory design.  The findings of this research are based on in-depth interviews conducted among horticulture farmers in the Mutoko district.  The significance of embracing Indigenous Knowledge Systems (IKS) in entrepreneurship among horticulture farmers in the Mutoko district was examined. Horticulture is a popular kind of farming in the region, with farmers specializing in tomatoes, cucumbers, leafy vegetables, onions, and butternut.